KONDISI SOSIAL EKONOMI DAN PERSEPSI MASYARAKAT TERHADAP PERUSAHAAN (STUDI TENTANG PENGARUH KEBERADAAN PT.RIAU ANDALAN PULP AND PAPER DI MASYARAKAT KELURAHAN PANGKALAN KERINCI BARAT LINGKUNGAN TERUSAN BARU KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN) - Wati, Ria Ratna; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in the village of Pangkalan Kerinci Western District of Pangkalan Kerinci Pelalawan aimed to determine the socio-economic conditions of society in Pangkalan Kerinci West Village. This study, entitled "Socio-Economic Conditions and Public Perception Of The Company (Study on Impact of PT.Riau Andalan Pulp and Paper On Barat Urban Village Community Environment Pangkalan Kerinci New Canal District of Pangkalan Kerinci Pelalawan) ''. The principal issues in this study for how the socio-economic conditions of society and to how the public perception of PT. Riau Andalan Pulp and Paper which is located in the West Village neighborhood Pangkalan Kerinci New Canal in the district of Pangkalan Kerinci Pelalawan in the community. The population in this study is the head of household or housewives who make a living in the West Village neighborhood Pangkalan Kerinci New Season. samples in this study is the simple random sampling technique. Total population in this study in 2014 amounted to 750 heads of families, a swab 50 families or housewives who have represented from the specified population. The method used is descriptive quantitative method with the quantitative and qualitative analysis. Data filtering instruments used are interviews, questionnaires, observation, documentation, and key-informant. As well as presenting the results of processing the data in tabular form. The theory used in this study the socio-economic factors that determine the socio-economic and basic concepts of perception. Based on this research, public relations Pangkalan Kerinci West Village neighborhood New canal either, be the one to keep the existence of the company PT.RAPP. In this study, the factors are the socio-economic impact and public perception.Keywords: Socioeconomic, Perception